MULTIPLE GENERATIONS OF FAULTING: A KINEMATIC ANALYSIS OF THE LAGARFLJÓT REGION, NORTHEAST ICELAND - Runnals, Keegan (SURFACE at Syracuse University, 2015)
The North American/Eurasian plate boundary in Iceland is structurally diverse with oblique rifts, volcanic fissure swarms, and transform zones, and a hotspot. Lagarfljót is a lake located in the Tertiary flood basalts of East Iceland, that range in age from ~7 to 3 Ma. The lake is approximately 50 km east of the actively spreading, NS-trending, Northern Rift Zone (NVZ), and occupies a northeast-trending depression in an area of strong NS lineaments. A flexure zone, or zone of steeply dipping lavas, runs N-S across the southern part of the lake, and predates an angular unconformity in the regional lava pile. A detailed investigation of fault zones in exposures in cliffs along the lakeshore and streams reveal a series of dikes and faults. These dikes and faults can be correlated with the lineaments, and indicate a complicated tectonic history. Fault zones are characterized by fault breccia, cataclasite and gouge with well-developed slickenlines and clear shear-sense indicators. Fault gouge in individual shear zones range in thickness from centimeters to meters. Cross cutting relationships define the relative ages of two families of structures, both post-dating the flexure. The older generation of faults are NS-striking, dextral, strike-slip faults. These are cut by NE-striking, normal faults. The normal faults typically cut existing large dikes or swarms of dikes ranging from 1 – 5 m wide. Displacements along individual normal faults range from centimeters up to 8 m. Some faults cut the lavas above the unconformity and locally rotated structures suggest that limited tilting of the lava pile occurred during faulting. These findings are evaluated with respect to larger scale processes of propagation and relocation of the NVZ.